2014
DOI: 10.1007/s12206-014-0818-7
|View full text |Cite
|
Sign up to set email alerts
|

Stall inception and warning in a single-stage transonic axial compressor with axial skewed slot casing treatment

Abstract: Characteristic changes in the stall inception in a single-stage transonic axial compressor with an axial skewed slot casing treatment were investigated experimentally. A rotating stall occurred intermittently in a compressor with an axial skewed slot, whereas spike-type rotating stalls occurred in the case of smooth casing. The axial skewed slot suppressed stall cell growth and increased the operating range. A mild surge, the frequency of which is the Helmholtz frequency of the compressor system, occurred with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…CTs can be broadly classified into two categories: groove type 19–21 and slot type. 2224 Takata 25 experimentally investigated CTs using low-speed compressors. The results indicated that slot-type CTs could provide a larger stall margin improvement, among which the skewed slots showed the best improvement.…”
Section: Introductionmentioning
confidence: 99%
“…CTs can be broadly classified into two categories: groove type 19–21 and slot type. 2224 Takata 25 experimentally investigated CTs using low-speed compressors. The results indicated that slot-type CTs could provide a larger stall margin improvement, among which the skewed slots showed the best improvement.…”
Section: Introductionmentioning
confidence: 99%
“…57 Moreover, the TLF becomes increasingly unsteady during the throttling process and oscillates at the near-stall point in axial compressors (whether single or multistage, low or high speed), which is probably associated with the onset of instabilities in aero-engine compressors. 814…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these techniques were not widely used in compressors. Continuous improvement in the understanding of the mechanisms underlying the casing treatments [7][8][9][10][11] and stall inceptions [12][13][14] yielded vast explorations of active control. This strategy comprised the detection of the onset of rotating stall or surge and the execution of tip injection with a feedback control loop.…”
Section: Introductionmentioning
confidence: 99%